Knockdown of LncRNA H19 inhibits vascularization and endochondral ossification via the MiRNA-21a-5p-Smad7/p-Smad2/3 pathway in fracture repair - Qiuyue Sun; Chen Zhang; Bowen Chen; Junyi Liao; Aowen Bao; Chen Zhao; Hong Chen; Dawei He; Wei Huang; Guangming Dai (Scientific Reports)
Abstract The biological process of fracture repair involves inflammation, vascularization, endochondral ossification, and cartilage production. Long non-coding RNAs (lncRNAs) are essential for the growth and maintenance of the skeleton. In this study, the role of the long non-coding RNA H19 in endochondral ossification during fracture repair was investigated. We examined H19 expression in the contexts of skeletal development and fracture repair and found that hypertrophic chondrocytes, growing endochondral bone spongiosa, and cortical bone exhibit H19 expression. H19 expression in cortical bone was similar to that in skeletal muscle, suggesting a potential role in bone development regulation. Inhibiting H19 near fractures in a mouse model resulted in disruption of vascularization and delayed endochondral ossification, ultimately leading to delayed fracture union. Importantly, H19 inhibition had no impact on the formation of the cartilaginous callus, indicating its specific role in vascularization and ossification. Further analysis revealed that H19 reduced miR-21a-5p’s inhibition of smad7 by functioning as a sponge for miR-21a-5p. H19 silencing led to a decrease in Smad7 expression and a rise in Smad2/3 phosphorylation, and delayed both ossification and vascularization. In conclusion, H19 influences bone remodeling and fracture healing by modulating the miR-21a-5p-smad7-TGFβ-smad2/3 axis, presenting therapeutic potential for fracture repair.